2014
DOI: 10.1124/dmd.113.055590
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cassette Dosing Approach to Examine the Effects of P-Glycoprotein on the Brain and Cerebrospinal Fluid Concentrations in Wild-Type and P-Glycoprotein Knockout Rats

Abstract: The study objectives were 1) to test the hypothesis that the lack of P-glycoprotein (P-gp) and the inhibition of breast cancer resistance protein (Bcrp) at the blood-brain barrier after cassette dosing of potent P-gp and Bcrp inhibitors were due to low plasma concentrations of those inhibitors and 2) to examine the effects of P-gp on the unbound brain (C u,brain ) and cerebrospinal fluid (CSF) concentrations (C u,CSF ) of P-gp substrates in rats. In vitro inhibition of 11 compounds (amprenavir, citalopram, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…The magnitude of the increase in brain exposure of loperamide in the Mdr1a(À/À) rats was similar to that observed in Pgp-deficient mice (Uchida et al, 2011) and was in good agreement with what Bundgaard et al (2012) and Liu et al (2014) reported recently. It was previously reported that dantrolene brain exposure increased 3-and 6-fold in Abcg2(À/À) mice following an IV bolus dose or IV infusion, respectively (Enokizono et al, 2008;Xiao et al, 2012).…”
Section: Animalssupporting
confidence: 92%
See 1 more Smart Citation
“…The magnitude of the increase in brain exposure of loperamide in the Mdr1a(À/À) rats was similar to that observed in Pgp-deficient mice (Uchida et al, 2011) and was in good agreement with what Bundgaard et al (2012) and Liu et al (2014) reported recently. It was previously reported that dantrolene brain exposure increased 3-and 6-fold in Abcg2(À/À) mice following an IV bolus dose or IV infusion, respectively (Enokizono et al, 2008;Xiao et al, 2012).…”
Section: Animalssupporting
confidence: 92%
“…Tsuchiya et al (2014) recently reported that the mean CSF concentration (C CSF ) of raltegravir was significantly lower in patients with ABCG2 421AA genotype (510 ng/mL) compared to those with CC genotype (103.6 ng/mL). Though Pgp and BCRP at choroid plexus may pump drugs from the blood into the CSF compartment, the absence of Pgp and Bcrp in general increases drug concentrations in CSF samples collected from cisterna magna (Doran et al, 2005;Kodaira et al, 2011;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, SzolomajerCsikós et al (2013) also used a CAM efflux assay and found the IC 50 of Ko143 to be 8.74 6 0.29 mM for ABCB1 and 9.13 6 1.07 mM for ABCC1. In addition, 800 nM Ko143 partially inhibited basolateral to apical transport of amprenavir in cells overexpressing ABCB1 (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to a reservoir effect of poorly soluble Ko143 in vivo. Conversely, as part of a cassette dosing study, Liu et al (2014) could not detect Ko143 in plasma, brain, or cerebrospinal fluid at multiple time points (0.25, 1, and 3 hours) after 3 mg/kg dosing, and concluded that it was likely due to rapid clearance.…”
Section: Ko143 Not Specific For Abcg2mentioning
confidence: 99%
“…In addition, Bundgaard et al (2012) found that the brain distribution of several central nervous system drugs and active metabolites showed the same changes in brain penetration in rats as in mice when Mdr1a knockout animals were compared with wild-type animals. Liu et al (2014) have recently used a cassette-dosing approach to study BCRP and P-gp substrates and inhibitors in Mdr1a knockout rats.…”
Section: Introductionmentioning
confidence: 99%